The wife - Runge, Björn, 1961-; Close, Glenn, 1947-; Irons, Max, 1985-; McGovern, Elizabeth, 1961-; Slater, Christian; Pryce, Jonathan; Lloyd, Harry, 1983-; Wolitzer, Meg (Culver City, CA : Sony Pictures Home Entertainment, 2019)
The story of the couple's youthful passion and ambition interwoven with a portrait of a marriage, thirty-plus years later, a lifetime's shared compromises, secrets, betrayals, and mutual love.
Based on the novel by Meg Wolitzer.
Originally released as a motion picture in 2018.
Wide screen (2.40:1).
Glenn Close, Max Irons, Elizabeth McGovern, Christian Slater, Jonathan Pryce, Harry Lloyd.
MPAA rating: R.
DVD, region 1, NTSC, wide screen (2.40:1); Dolby digital.
Keywords: Drama films